Consumer's Environmental Awareness and the Role of (Green) Entrepreneurship: Lessons from Environmental Quality Competition and R&D Activities for Environmental Policy - Torben Klarl (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
In the recent last years, in particular in the aftermath of the global financial and economic crisis, many countries initiated economic recovery plans with a major focus on stimulating green entrepreneurial activities to revive economic growth. Further, the recovery plans intend to improve a country's awareness for a direct orientation towards (strong) sustainability and green growth. Before discussing strategies towards green growth, in this paper we propose a novel framework to increase our understanding of the interplay of process R&D activities, the strategic price and environmental quality setting of heterogeneous entrepreneurs in a market where consumers feel up to paying for environmental quality improvement of a vertically differentiated good. In the paper we decompose an entrepreneur's incentive conducting process R&D in four parts. In particular we show that an entrepreneur's incentive of conducting own process R&D is reduced due to the existence of knowledge-spillovers. Moreover, due to the strategic complementarities, both in prices as well as in environmental quality, a strategic effect reinforces the negative consequences of the spillover-effect. We show that the externalities in the model require corrections based upon a mixture of fiscal policies and a process R&D subvention scheme establishing a first-best solution. We further thoroughly discuss the implementation of a second-best solution and derive environmental policy implications.
Keywords: Q55; Q58; O31; 330